2011
DOI: 10.1159/000327709
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Functional Analysis of Dkk1 during Early Gonadal Development

Abstract: Development of the bipotential mouse gonad into either a testis or an ovary depends on a transcriptional balancing act [Kim and Capel, 2006]. Testis development is triggered by SRY, the Y-chromosomal testis-determining factor, which needs to upregulate genes such as Sox9 and Fgf9 early enough and strongly enough to overcome the ovarian program of development. Conversely, the testicular program can be overcome to some extent by the actions of ovarian secreted factors RSPO1 (roof plate-specific spondin 1) and WN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 81 publications
0
12
2
Order By: Relevance
“…As such, both DKK1 and DACT1 enable the axin/ Gsk3/APC complex to degrade β-catenin and minimize the expression of β-catenin/LEF/TCF-responsive genes, resulting in a different cell type than those lacking either DKK1 or DACT1. DKK1 has been found to play a role in normal development of testis in mice Combes et al, 2011]. But unlike mice, we found that dkk1 was upregulated in ovaries rather than testes.…”
Section: Discussioncontrasting
confidence: 63%
“…As such, both DKK1 and DACT1 enable the axin/ Gsk3/APC complex to degrade β-catenin and minimize the expression of β-catenin/LEF/TCF-responsive genes, resulting in a different cell type than those lacking either DKK1 or DACT1. DKK1 has been found to play a role in normal development of testis in mice Combes et al, 2011]. But unlike mice, we found that dkk1 was upregulated in ovaries rather than testes.…”
Section: Discussioncontrasting
confidence: 63%
“…qRT-PCR is commonly used to study gene expression during gonadogenesis (Abramyan et al 2009;Barrionuevo et al 2006;Barske and Capel 2010;Beverdam and Koopman 2006;Bogani et al 2009;Bouma et al 2005Bouma et al , 2007Bradford et al 2009;Britt et al 2002;Chang et al 2008;Chassot et al 2008;Chen et al 2012;Childs et al 2011;Combes et al 2011;Cupp et al 2003;DeFalco et al 2014;Hiramatsu et al 2009;Houmard et al 2009;Koubova et al 2006;Li et al 2012;Liu et al 2015;Maatouk et al 2008;Manuylov et al 2007;Molyneaux et al 2003;Moniot et al 2009;Munger et al 2013;Nef et al 2003Nef et al , 2005Nicol and Yao 2015;Parma et al 2006;Rolland et al 2011;Ross et al 2009;Smith et al 2008aSmith et al , b, 2009Tang et al 2008;Tevosian et al 2002;Wilhelm et al 2005). In the majority of studies of gonad development, primers labeled with SYBR Green fluorochrome are used although TaqMan probes have also been applied Liu et al 2015;Smith et al 2008a, b).…”
Section: Pcr-based Methods Of Gene Expression Analysismentioning
confidence: 99%
“…The first report of detection of DNA:RNA hybridization was given by Gall and Pardue (1969). This method is frequently used in gonadal development studies in both the post-embedding version (ISH) (Abramyan et al 2009;Best et al 2008;Bradford et al 2009;Chassot et al 2008;El Jamil et al 2008;Hanley et al 2000;Kim et al 2006;Maatouk et al 2008;Martineau et al 1997;Matzouk et al 1995;Moniot et al 2009;Morais da Silva et al 1996;Nef et al 2003;Oulad-Abdelghani et al 1996;Parma et al 2006;Schmahl et al 2004;Sekido et al 2004;Wilhelm et al 2005) and pre-embedding or whole mount-ISH (WM-ISH or WISH) (Barrionuevo et al 2006;Bishop et al 2000;Bogani et al 2009;Combes et al 2009aCombes et al ,2011Coveney et al 2008;Jameson et al 2012;Koubova et al 2006;Manuylov et al 2007;Matsuyama et al 2005;Nef et al 2005;Rolland et al 2011;Smith et al 2008a, b;Stebler et al 2004). The core idea in the ISH technique is the hybridization of a labeled complementary probe to mRNA allowing the identification of a specific gene transcript under a microscope.…”
Section: Identification Of Mrna: In Situ Hybridizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Dkk1 (Dickkopf homologue 1) served as a control as it is enriched in the embryonic testis [37,38] . It was in fact robustly expressed in the WT embryonic testes, not detected in the WT ovaries, and reduced in the Wnt-4-deficient testes ( Fig.…”
Section: Wnt-4 Signalling Also Controls the Genes Associated With Thementioning
confidence: 99%